A New Rabbit-Skin Model to Evaluate Protective Efficacy of Tuberculosis Vaccines - Chen, Huiyu; Liu, Xun; Ma, Xingming; Wang, Qian; Yang, Guang; Niu, Hongxia; Li, Shuaixiang; He, Bingzheng; He, Shanshan; Dannenberg, Arthur M.; Zhu, Bingdong; Zhang, Ying (Frontiers in Microbiology, 2017)
Background: BCG protection is suboptimal and there is significant interest to develop new tuberculosis (TB) vaccines. However, there are significant limitations of the current vaccine evaluation systems in the mouse model. Here we developed a BCG-challenge rabbit skin model as a new way to evaluate the protective efficacy of selected TB subunit vaccine candidates. Methods: Rabbits were immunized with subunit vaccines, including EAMM (ESAT6-Ag85B-MPT64<190-198>-Mtb8.4), MH (Mtb10.4-HspX) and LT70 (ESAT6-Ag85B-MPT64<190-198>-Mtb8.4-Rv2626c) three times subcutaneously every three weeks and challenged with the attenuated Mycobacterium bovis BCG intradermally six weeks after last immunization. The immune response induced by the vaccine candidates was measured, the histopathology induced by the BCG challenge was studied, and the number of bacilli in the liquefied caseum was determined. Results: The subunit vaccines generated high antigen-specific IgG antibodies and fastened the liquefaction and healing process, and significantly reduced the viable BCG load. The subunit vaccine LT70 and EAMM-MH reduced BCG bacterial load in comparison to proteins EAMM, MH, Rv2626c and also BCG itself. The Koch phenomena induced by the LT70 and combination of EAMM-MH were the same as that produced by BCG itself and were more rapid than those induced by the other proteins and the saline controls. Conclusions: The subunit vaccines LT70 and the combination of EAMM-MH showed promising protective efficacy as expected in the rabbit skin model, which can serve as a visual and convenient new model for evaluating TB vaccines.